Presence of Inguinal Hernia in Soccer Players with Osteitis Pubis - Ali Eraslan (Spor Hekimligi Dergisi, 2017)

(untitled)
Objective: Groin pain is one of the most important health problems in soccer. Its causes include musculo-tendinous injuries, osteitis pubis, inguinal hernia, sports hernia, avulsion fractures, hip pathologies and urogenital problems. In this study, it was aimed to investigate the presence of inguinal hernia in soccer players with osteitis pubis. Material and Methods: Archive records of male soccer players who were admitted to the sports medicine clinic with groin pain, and diagnosed with osteitis pubis were screened retrospectively. Pelvic MR images and inguinal USG results were reviewed. Results: A total of 51 soccer players with osteitis pubis were detected in the archive records. There were eight osteitis pubis cases (15.6%) associated with inguinal hernia. Three athletes (5.8%) had undergone hernia operation before admission. The remaining five (9.8%) were concomitant cases of inguinal hernia and osteitis pubis. In seven of the eight cases, ipsilateral findings of osteitis pubis were more severe than those with contralateral hernia. Conclusion: The study revealed that soccer players with osteitis pubis may have concomitant inguinal hernia, and that osteitis pubis may develop in soccer players who have undergone hernia repair. In addition, more severe osteitis pubis findings on the same side with hernia indicate that the two pathologies occur with common mechanisms. It should not be forgotten that inguinal hernia be considered in the differential diagnosis of osteitis pubis, which it may accompany. Conservative methods are mostly used in the treatment of osteitis pubis, whereas the treatment of inguinal hernia is surgery. If only one entity is diagnosed when both are present, the success of treatment will decrease.